El principio de precaución en salud como pilar del control constitucional en Colombia (Tema Central) - Ortega Rodríguez, Camilo Ernesto (2021)
The article comments on the jurisprudence of the precautionary principle on the right to health. This is done in order to identify a constitutional basis that allows for the implementation of various protective measures, despite the lack of 100 percent scientific certainty in some cases. For this purpose, a dogmatic and non— formal method will be used, focusing the study of the problem from a theoretical point of view, but maintaining contact with the factual and social reality of the problem. As a technique, data collection is used, mainly the jurisprudence of the Colombian Constitutional Court and academic articles that allow for the contextualization of the development of the principle. The result of the research allows us to observe the application of the precautionary principle in health due to the use of glyphosate or the transport of coal, as well as in the face of hydrocarbon exploitation and even the installation of mobile telephone antennas. The article concludes that, in view of the unpredictability of scientific development, the pertinent thing to do is to apply the necessary measures to prevent the occurrence of damage or risk to rights, for which the precautionary principle is the most solid and rational basis to be developed.